Pengaruh Kompetensi Pramuwisata Arung Jeram Terhadap Kepuasan Wisatawan di Sungai Citarik Kabupaten Sukabumi - Mulyana, Hadi (Manajemen dan Pariwisata, 2024)
Rafting is one of the sport challenge and it has high rish. It is necessary need guide security an safety procedures before doing rafting. Rafting guide is needed in his activity and it must has acompetency. This research uses a simple regression analysis techniques, the variabels tha is used are competency assembling influences positively and significantly toward the tourist satisfaction as hypothesis through verificative and descriptive quantitative method. The total sample of this research is 98 respomdemts through simple random sample method. The instrument that is used to collect the data is questionnaires. The result shows that the all questions are valid above 0,30 and reliable because it is above 0,70. As descriptively, the competency is generally “good” with average3,64 of 1-5 scale and the tourist satisfaction visit shows “good anough” result with average 3,15 of scale 1-5 scale. Mean while. The result of verificative analysis show determination coefficient (R2) in the amount of 0,370 or 37%, the rest (epsilon) is 63% which is other variabel that has not been researched. The result of the hypothesis examine shows that there are positive and significant influence among the variabels of competence toward the variabel satisfaction of tourist, which the significancy either partially (t test) and simultaneous (F test) is 0,000 less than 0,05.